تقويم تعليم اللغة العربية - Risalatul Muawanah; Nihayatus Sa’diyah; Zakiyah Isnawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2019)
Evaluation is a very urgent part of the process of learning Arabic. In the relationship between evaluation and learning Arabic, i.e. can be known to what extent the success of the learning process and the learning objectives to be achieved. Therefore, every Arabic language teacher must have the knowledge and understanding of the criteria and principles for preparing an evaluation instrument for learning Arabic. In order for the test to have good quality, three criteria must be fulfilled, namely validity, reliability, and practicality. The Arabic language test room can be grouped into two: namely language element tests and language skills tests. Arabic tests can be grouped into various types of tests based on various characteristics of grouping. In preparing the Arabic language test, it is necessary to pay attention to the principles and guidelines for the preparation of the test so that the test questions prepared are guaranteed quality.